"Diabetic striatopathy" and ketoacidosis: Report of two cases and review of literature. (June 2017) - Das, Liza; Pal, Rimesh; Dutta, Pinaki; Bhansali, Anil
Highlights: "Diabetic striatopathy" denotes a clinico-radiologic syndrome of chorea-ballism and striatal hyperintensities on MR imaging. It is common in elderly females with hyperglycemic hyperosmolar state but rare in diabetic ketoacidosis. Chorea-ballism usually resolves with intensive management of diabetic ketoacidosis. Abstract: "Diabetic striatopathy" is characterized by dyskinesias with basal ganglia hyperintensities on neuroimaging. It is usually reported in elderly females with hyperglycemic hyperosmolar state and rare in patients with diabetic ketoacidosis. Here, we report two young males with diabetic ketoacidosis presenting as striatopathy, along with review of literature.